Foreign Policy Posture in Post-Apartheid South Africa : Consistencies and Ambiguities - Mngomezulu, Bhekithemba R. (Newcastle upon Tyne, UK : Cambridge Scholars Publisher, 2023)
Foreign policy and domestic policy feed into each other. To a large degree, the latter informs the former. This book demonstrates the relationship between the two, paying particularly close attention to how South Africa envisioned its foreign policy during the negotiation process.
Includes bibliographical references and index.
Keywords: Since 1994; 1994-; Diplomatic relations; International relations; South Africa -- Foreign relations -- 1994-; South Africa; Print books